Diamond Detector Development for Neutron Measurements at the n_TOF Facility (CERN) - Kaperoni, Kalliopi; Diakaki, Maria; Bacak, Michael; Weiss, Christina; Griesmayer, Erich; Jericha, Erwin; Kokkoris, Mike; Kopsalis, Ioannis; Melbinger, Julian; Collaboration, n_TOF (HNPS Advances in Nuclear Physics, 2026)
Diamond is a highly promising material for neutron detection due to its radiation hardness, fast response, and high signal-to-noise ratio. A single-crystal diamond (sCVD) detector with a 6LiF conversion layer was developed in collaboration with CIVIDEC Instrumentation for in-beam measurements at the n_TOF facility at CERN. The effect of the diamond detector thickness on the response to 𝛾-rays was studied with a 137Cs source. Additionally, measurements with thermal neutrons at the TRIGA reactor (Atominstitut Vienna) confirmed the proper detection of the recoils of the 6Li(n,t)4He reaction, by the developed detection system. In-beam tests at the EAR2 experimental area demonstrated stable performance under a white neutron beam, while the final easurement at the NEAR station validated the detector’s suitability for neutron flux characterization in challenging high-radiation environments.